2008
DOI: 10.1093/intimm/dxn018
|View full text |Cite
|
Sign up to set email alerts
|

Differential influence of the tumour-specific non-human sialic acid containing GM3 ganglioside on CD4+CD25- effector and naturally occurring CD4+CD25+ regulatory T cells function

Abstract: Increasing evidences suggest that the aberrant expression of certain gangliosides on malignant cells could affect host's anti-tumour-specific immune responses. We have recently documented the relevance of the N-glycolylated variant of GM3 ganglioside (NGcGM3), a tumour-specific non-human sialic acid containing ganglioside, for tumour progression. However, evidences about the implication of host's immunity in NGcGM3-promoted cancer progression had not been obtained previously. In this work, we compared tumour g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 32 publications
1
28
0
Order By: Relevance
“…Recent results indicated that NeuGcGM3 contribute to cancer progression mainly by influencing DC and CD4 + CD25 -T lymphocyte functions, rather than increasing the inhibitory capacity of naturally occurring regulatory T cells. 6 The relevance of these three patients developed vitiligo at the lower dose, although the nominal antigen NeuGcGM3 was not present in melanocytes. Safety and immunogenicity with NeuGcGM3 vaccine treatment in advanced melanoma patients were established.…”
Section: Immunogenicity and Safety Of A Neugcgm3 Based Cancer Vaccinementioning
confidence: 88%
See 3 more Smart Citations
“…Recent results indicated that NeuGcGM3 contribute to cancer progression mainly by influencing DC and CD4 + CD25 -T lymphocyte functions, rather than increasing the inhibitory capacity of naturally occurring regulatory T cells. 6 The relevance of these three patients developed vitiligo at the lower dose, although the nominal antigen NeuGcGM3 was not present in melanocytes. Safety and immunogenicity with NeuGcGM3 vaccine treatment in advanced melanoma patients were established.…”
Section: Immunogenicity and Safety Of A Neugcgm3 Based Cancer Vaccinementioning
confidence: 88%
“…from breast cancer patients vaccinated with NeuGcGM3/VSSP plus Montanide ISA51 in a previous clinical trial. 6 Nonetheless, the molecular pathway that is activated under polyclonal NeuGcGM3-specific antibodies effect remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 NGcGM3 contributes to cancer progression, not only by influencing dendritic cell differentiation and maturation, but also down-modulating the CD4 expression in T cells 10 and impairing CD4 + CD25 -T lymphocyte functions. 11 Many clinical trials have been performed with a NGcGM3-containing vaccine for the immunotherapy of melanoma [12][13][14][15] and breast cancer. 16,17 The vaccine consisted in very small sized proteoliposomes (VSSP) obtained by the incorporation of the NGcGM3 ganglioside into the outer membrane protein (OMP) complex of Neisseria meningitides.…”
Section: Introductionmentioning
confidence: 99%